Bahasa, Teknologi, dan Manipulasi Digital: Analisis Filsafat Bahasa dalam Iklan Pinjaman Online di Era Digital - Lestari, Tri Edliani (Program Studi Magister Linguistik Terapan UNJ, 2023)
The phenomenon of the rise of online loan advertisements in Indonesia shows a close relationship between the use of language and its influence on people's behavior. This study aims to analyze the influence of language used in online loan advertisements on the increasing trend of online loans in Indonesia. In addition, this study also aims to distinguish the characteristics of language used in legal online loan advertisements under the supervision of the Financial Services Authority (OJK) and illegal ones. With a qualitative-descriptive approach, this study explores how digital technology influences the language style in online loan advertisements and its implications for people's decisions. The results show that online loan advertisements use persuasive language strategies, often emphasizing convenience, speed, and flexibility, but differ in terms of legality. The language in legal advertisements tends to be more transparent and informative, while in illegal advertisements it is more manipulative and misleading. This study is expected to contribute to the understanding of the relationship between language, digital technology, and consumer behavior in the context of the philosophy of language.